Emerging markets portfolio. - Hee, Alex Guo Quan. (2008)
This paper aims to evaluate the performance of an 'Emerging Markets Portfolio', constructed with an active strategy. The results of this study indicated that the simulated portfolio outperformed three benchmarks in terms of the Sharpe Model Index over the period 1 January 1993 to 31 December 2002.